Compensation management on employee job satisfaction at CIMB call centre in Kuala Lumpur - Nur Afiqqah, Mohamad Eskandar (2018)
Compensation management is the process that provides monetary value to employees. This includes base salary, performance bonuses, health insurance and retirement plans. The aims of this study are to know the compensation management on employee job satisfaction at CIMB call centre in Kuala Lumpur. Besides that, the researcher would like to determine the factors by which gives an important impact towards their job’s satisfaction such as compensation policy design, awareness of compensation packages, compensation packages and management and communication. The objectives of this study is to determine the level of job satisfaction among employee at CIMB call centre in Kuala Lumpur, to determine the relationship between compensation policy design and job satisfaction among employee at CIMB call centre in Kuala Lumpur, to determine the relationship between awareness of compensation package and job satisfaction among employee at CIMB call centre in Kuala Lumpur, to determine the relationship between compensation package and job satisfaction among employee at CIMB call centre in Kuala Lumpur, to determine the relationship between Management and Communication and job satisfaction among employees at CIMB call centre in Kuala Lumpur and to determine the effect of compensation management on employee job satisfaction among employees at CIMB call centre in Kuala Lumpur. About 156 of call centre employees involved in this study. This finding of research discovered that all independent variables have significant relationship and affect the job satisfaction.